Robotics in Sri Lanka: Current Status and Future Potential - W.S.S.Perera; Prabodha Lenora (International Journal of Engineering and Management Research, 2022)
Sri Lanka is a technological leader around the globe. As a result, Sri Lanka’s software sector is conducting several trials with Artificial intelligence, machine learning, and the Internet of Things. This study places an emphasis on the application of artificial intelligence in a major domain, robotics, which will have a significant impact in Sri Lanka in the near future. Starting from an introduction to the robotics domain in Sri Lanka, we discuss what is robotics, the impact of robotics in the world, and Sri Lanka in brief. This paper examines the current state of robotics in Sri Lanka, with a focus on its potential for economic and technological development. We review the existing research and development initiatives in robotics and identify the key challenges and opportunities facing the field in Sri Lanka. We also discuss the potential applications of robotics in various sectors, including manufacturing, agriculture, healthcare, and education. Through a review of the literature and interviews with industry experts, we aim to provide a comprehensive overview of the current state and future prospects of robotics in Sri Lanka. The most important and popular robotics implementations are selected and further analyzed. Then the significance and contribution of those two studies to robotics are analyzed with advantages and disadvantages for robotics domain in Sri Lanka. Next, the technologies and key algorithms are discussed in light of recent research. Finally concludes with future works and robotics barriers in Sri Lanka.